Engaging E-Lectures Blended Course with Problem Based Learning Activities at a Developing University - Djoko Sutrisno (ETERNAL (English Teaching Journal), 2015)
The research setting for much of the investigation of the mixing e-lectures blended with Problem Based Learning is in English Department of Ma’arif Nahdlatul Ulama of Kebumen (UMNU). The research focus is on expending technology e-lectures to maintenance the student of English Department blended Problem Based Learning (PBL), which the participants assumed in cooperative groups. Video-based e-lectures offer interactive learning and more bright and adapted forms of self-regulated learning. Participants learned from both a video-based e-lecture with synchronized written transcript of oral presentation (multimodal) and an e-lecture without the transcript (unimodal presentation). Learners could be categorized as “repeaters”, whose main focus was on th e lectured material, or as “surfers,” who consumed less time on the lecture itself and as an alternative used the optional links. The Student of English Department was conveyed using a blend of face-to-face and online Problem-based Learning. By exploring key proficiencies concerning the integration of a variability of learning technologies in these courses an exertion is being made to control how the teacher’s role can design for effective integration of technology into the curriculum. While a blend of new media can suggestion significant occasions for lecturers in higher education, this can also be a discouraging obstacle for strangers. Subsequently it is expected that what is presented here in terms of the capability from these courses, can contribution academic staff in feeling at easiness with using a variety of learning technologies to support e-lecturer and Problem-based Learning and reproduce that in their own teaching practice in their disciplines. Results showed that the learning outcomes were significantly influenced by learner strategy (with repeaters outclassing surfers) using a range of learning technologies to support e-lect